Aqueous polyacrylate latex nanodispersions used as consolidation agents to improve mechanical properties of Prague sandstone - Sevcik, Radek; Machotová, Jana; Zarybnicka, Lucie; Macova, Petra; Viani, Alberto (Elsevier France, 2023)
This investigation aims at assessing the potential of polyacrylate latex nanodispersions as consolidation agents for sandstones. Four different latex types, implementing polymer fluorination and chemical crosslinking, have been synthesized at the scope and fully characterized. The Prague sandstone employed in this study has been selected as an example of highly porous stones used as building materials for many historical monuments. Two different concentration levels of nanodispersions have been adopted. The consolidated stone samples have been tested using a combination of physical-mechanical tests and microscopic observations. Compared to the non-treated samples, significant increments of mechanical properties ( e.g. up to 3.3 times higher bending strength) have been detected after the consolidation treatment with concentrated products. Moreover, when 10 times diluted latex nanodispersions have been applied, the improvement of mechanical properties has still been significant, while moisture transport properties, such as water absorption, have been found to be comparable with those of the untreated sample. Fluorinated polymers imparted better hydrophobic properties with a contact angle above 100 & DEG;. Observations using a scanning electron microscope revealed the good filling and bridging capacity of the applied consolidation agents. As demonstrated, by acting on the polymer structure, that is, by tuning the degree of crosslinking, polymer fluorination and gel content, the properties of these novel polyacrylate latex nanodispersions can be tailored to the specific stone and type of decay in order to improve the effectiveness of the treatments and obtain the desired final properties. The flexibility of their chemistry offers new opportunities for preserving objects of cultural heritage that are also at risk due to the ongoing climate change.& COPY; 2023 Consiglio Nazionale delle Ricerche (CNR). Published by Elsevier Masson SAS. All rights reserved.
Vodné polyakrylátové latexové nanodisperze používané jako konsolidační činidla pro zlepšení mechanických vlastností pražského pískovce
Keywords: Polyacrylate latex; Consolidation; Prague sandstone; Mechanical properties; Hydrophobicity; Polyakrylátový latex; Konsolidace; Pražský pískovec; Mechanické vlastnosti; Hydrofobicita